Nursing problems in a patient with cancer of the cervical spinal cord - Kozera, Marzenna; Napierała, Marek; Muszkieta, Radosław; Zukow, Walery (Journal of Education, Health and Sport, 2011)
Neoplastic lesions of the cervical spinal cord, are much less frequently than intracranial tumors. Aim of this study was to present the most important nursing problems, which can meet with the nurse taking care of the quadriplegic patient with paralysis. Presented case study patient treated surgically for tumors of the cervical spinal cord. Patient care discussed completely immobilized, only passing a care nursing staff. In the process of care should pay particular attention to: the prevention of cardiovascular and respiratory disorders, prevention of decubitus changes, preventing inflammation of the bladder and prevent pulmonary embolism. It is very important to include early physical rehabilitation and psychological care of patients and their families.